Is nephrostomy tube a rule following all Percutaneous Nephrolithotomy (PCNL)? A prospective randomized study - Chalise, Pawan Raj; Luitel, Bhojraj; Chapagain, Suman; Poudyal, Sujeet; Gyawali, Prem Raj; Sharma, Uttam Kumar; Joshi, Bhola Raj (Journal of Society of Surgeons of Nepal, 2017)
Introduction: Exit strategy at the end of percutaneous nephrolithotomy (PCNL) differs from center to center and patient to patient. Standard PCNL has been practiced so far with minor postoperative morbidities. Tubeless PCNL, which obviates most of the nephrostomy related morbidities, has been challenged for its safety. So this study was conducted to compare the safety and morbidity of tubeless PCNL with standard PCNL. Methods: Patients who had undergone PCNL, were randomized into group 1 (standard) and group 2 (tubeless) using computer generated random table. In group 1, nephrostomy tube was placed at the end of the procedure and tubes were omitted in group 2 patients. All preoperative, intraoperative and postoperative parameters were recorded and compared in between the groups. Results: Ninety six PCNLs were randomized into group 1 (47 patients) and group 2 (49 patients). Patients’ characteristics including age, sex, comorbidities, preoperative parameters, size and number of stones and mean operation time were comparable in between the groups. The incidence of postoperative fever, pain and analgesic requirement and urinary leak were found more in group 1 patients. The incidence of postoperative complications and events were comparable in both the groups except for blood transfusion. The mean length of postoperative hospital stay for patients in group 2 was significantly low as compared to group 1. Conclusion: Tubeless PCNL is safe and has less morbidity as compared to standard PCNL in selected cases.